Methodologie et resultats des essais d`adaptabilite du haricot en milieu rural, 1986 - Graf, W; Dessert, K; Nyabyenda, P (International Center for Tropical Agriculture, 1986)
On-farm trials were established by the Institut des Sciences Agronomiques du Rwanda (ISAR) to test bean adaptability in various sites with different agroecological conditions. The farmer`s cultural techniques regarding planting density and date, sowing method, and crop cultivation were strictly respected. In the high and middle altitude regions, yields of bean var. introduced by the ISAR were usually lower than those from the farmer`s mixture whereas in low altitude regions (Muhazi), var. Kilyumukwe yielded 43 percent more than the local mixture. This var. was also highly appreciated by farmers at harvest time; observations during the 1st semester of 1987 indicated that it was often replanted and disseminated. Based on these results, bean var. Kilyumukwe is recommended for dissemination in the Eastern Plateau. (CIAT)